Functional Outcomes of Dorsal Bridge Plating for Lisfranc Injuries with Routine Metalwork Retention: A Major Trauma Centre Experience. Issue 1 (January 2022) - Onochie, Elliot I.; Bua, Nelson; Patel, Amit; Jha, Shilpa; Heidari, Nima; Vris, Alexandros; Parker, Lee; Romans, Francesc Malagelada; Jeyaseelan, Luckshmana A.
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Lisfranc injuries represent a significant disruption to the complex articulations of the midfoot. Many of these injuries are unstable with displacement and articular incongruity. This necessitates surgical intervention with the primary goals of anatomic reduction and midfoot stability. Evidence around surgical treatments for Lisfranc complex injuries is limited by heterogeneity in outcome measures and small patient numbers. Dorsal bridge plating is a well-recognized surgical technique with the benefits of rigid stability and joint preservation. The primary aim of this study is to assess the midterm functional outcomes for patients treated with this technique at our major trauma centre. Additionally, we assess the complication profile and review for risk factors that influence the functional outcome. Methods: Eighty-five adult patients were identified as undergoing open reduction and dorsal bridge plate fixation for displaced, unstable Lisfranc injuries at our major trauma centre between January 2014 and January 2018. Supplemental Kirschner wire stabilization was used for the lateral column if necessitated by the injury pattern. Importantly, metalwork was not routinely removed. A retrospective review of case notes and imaging was conducted in order to collate demographic data including co- morbidities and smoking status. Patient-reported outcome measures were collected at final follow-up, with a minimum follow-up of 24 months. The Manchester-Oxford Foot Questionnaire summary index (MOXFQ-Index) was the primary patient-reported outcome. The American Orthopaedic Foot & Ankle Society (AOFAS) midfoot scale, complications, and all-cause re-operation rates were secondary outcome measures. Univariate and multivariate analyses were used to identify risk factors associated with poorer functional outcomes. Results: The mean follow-up in this study was 40.8 months (24 - 72). 61/85 patients (72%) had high-energy or crush mechanisms of injury. The mean MOXFQ-Index was 27.0 (SD 7.1). The mean AOFAS score was 72.6 (SD 11.6). 48/85 patients (56%) had injury patterns that included an intra-articular fracture and this was associated with poorer outcomes, with worse MOXFQ and AOFAS scores (both p<0.001). There were trends towards poorer outcomes in diabetic patients (p=0.07), those patients needing supplementary Lisfranc or intercuneiform screws (p= 0.39 and 0.45 respectively), and as a greater number of tarsometatarsal joints were stabilized (p=0.12). Overall, eighteen patients (21%) underwent removal of metalwork for either prominence or stiffness. Female patients were more likely to require metalwork removal (OR 3.89, 95% CI 1.27 to 12.0, p=0.02). Eight patients (9%) required secondary arthrodesis for post-traumatic osteoarthritis. Conclusion: This is the largest series of Lisfranc injuries treated with dorsal bridge plate fixation reported to-date. Bridge plating is safe and effective in stabilizing this complex midfoot injury. The presence of an intraarticular fracture is a poor prognostic indicator. This is the first study to report on outcomes with routine retention of bridge plates. 21% of patients required removal of metalwork and this was more likely in female patients. Patient-reported outcomes and secondary arthrodesis rates were comparable to the existing literature in which bridge plates are routinely explanted. This suggests that routine removal may not be a necessity.